2008
DOI: 10.1001/archinternmed.2007.39
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Physical Activity in Leisure Time and Leukocyte Telomere Length

Abstract: A sedentary lifestyle (in addition to smoking, high body mass index, and low socioeconomic status) has an effect on LTL and may accelerate the aging process. This provides a powerful message that could be used by clinicians to promote the potentially antiaging effect of regular exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
396
7
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(441 citation statements)
references
References 38 publications
18
396
7
14
Order By: Relevance
“…This trend toward longer telomeres was detected not only in the whole CD4 + and CD8 + T cell compartments but also in their respective CD45RO + /CD45RO neg and CD28 + /CD28 neg subsets, although statistical significance was observed only in the total CD8 + and CD8 + CD28 neg compartments between the IT and NT groups. These data are particularly important because previous studies on telomere length and physical activity showed conflicting results (Cherkas et al 2008;Ludlow et al 2008;Shin et al 2008;Woo et al 2008;Du et al 2012;Laine et al 2015). Comparisons among these studies are limited by differences in study design, including the immunological parameters assessed and the cohorts analyzed, which differed not only in age and gender but also in the type, intensity, and regularity of physical activity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This trend toward longer telomeres was detected not only in the whole CD4 + and CD8 + T cell compartments but also in their respective CD45RO + /CD45RO neg and CD28 + /CD28 neg subsets, although statistical significance was observed only in the total CD8 + and CD8 + CD28 neg compartments between the IT and NT groups. These data are particularly important because previous studies on telomere length and physical activity showed conflicting results (Cherkas et al 2008;Ludlow et al 2008;Shin et al 2008;Woo et al 2008;Du et al 2012;Laine et al 2015). Comparisons among these studies are limited by differences in study design, including the immunological parameters assessed and the cohorts analyzed, which differed not only in age and gender but also in the type, intensity, and regularity of physical activity.…”
Section: Discussionmentioning
confidence: 94%
“…Telomere shortening has been considered a marker of immunosenescence. The impact of regular exercise on telomere length remains controversial, with studies showing either no effect (Shin et al 2008;Woo et al 2008;Laine et al 2015) or a protective effect (Cherkas et al 2008;Ludlow et al 2008;Du et al 2012). Therefore, we measured and compared telomere length in total T cells [CD3 + ], CD4 + CD45RO + T cells, CD4 + CD45RO neg T cells, CD8 + CD28 + T cells, and CD8 + CD28 neg T cells among the groups.…”
Section: Telomere Lengthmentioning
confidence: 99%
“…Information on medication and supplement use, lifestyle, and demographic variables were obtained by standardized nurse‐administered questionnaire. Physical activity was classified as inactive, moderate, and active during work, home, and leisure time using a questionnaire strongly correlated with more in‐depth assessment of time spent in physical activity in this cohort 31. The mean time spent in physical activity per week for each physical activity level was as follows: inactive, 16 min; light activity, 36 min; moderate activity, 102 min; and heavy activity, 199 min.…”
Section: Methodsmentioning
confidence: 95%
“…24 For instance, telomere length varies individually and is under genetic control. 25 Further, variability of telomere length may be caused by influences of diet and physical activity, 26 psychological stress 27 and various diseases. [5][6][7][8]15,16,[22][23][24] Importantly, a recent report stated that in 850 Framingham Heart Telomere length in the LIFE studyStudy participants, leukocyte telomere length was positively associated with left ventricular mass and wall thickness, especially in participants with hypertension.…”
Section: Men Womenmentioning
confidence: 99%